Reductive Cross‐Coupling between Arylaldehydes and (Hetero)aryl Electrophiles Using Silylboronate Reductant. Issue 8 (21st February 2022) - Watanabe, Koh; Takeda, Mitsutaka; Nagao, Kazunori; Ohmiya, Hirohisa
Abstract: A catalytic reductive cross‐coupling between arylaldehydes and aryl electrophiles using a silylboronate as a terminal reductant is described. The reaction involves a copper‐catalyzed silylboration of aldehydes affording the O ‐borylated α‐silyl alcohols followed by a nucleophilic aromatic substitution reaction with aryl electrophiles. This protocol offers a new opportunity to access 1, 1‐diarylmethanol derivatives without rare metals or highly basic organometallic reagents. Abstract : This manuscript describes a catalytic reductive cross‐coupling between arylaldehydes and aryl electrophiles using silylboronate as a terminal reductant. The reaction involves a copper‐catalyzed silylboration of aldehydes affording the O ‐borylated α‐silyl alcohols followed by the nucleophilic aromatic substitution reaction with aryl electrophiles. This protocol offers a new opportunity to access 1, 1‐diarylmethanol derivatives without rare‐metals and highly basic organometallic reagents.